“I Pine for True Closeness”: Muḥammad Iqbāl’s Uneasy Relationship with Christianity, and the Islamic Social Ideal - Marjorie L. Corbman; Jan-Peter Hartung (South Asia Multidisciplinary Academic Journal)
In this article we examine the development of Muḥammad Iqbāl’s engagement with Christian thought and theology over the course of his lifetime in the context of his position as a colonial subject and of the rise of communalism and Muslim separatism in India. The early philosophical, spiritual, and poetic influence of European Christian authors on the young Iqbāl inspired him to develop a critique of Christian thought and history that fundamentally differentiated Christianity from Islam and positioned Islamic revelation as the truest origin of many of the ideals to which he was drawn in the works of Christian thinkers. Iqbāl mobilized his interpretation of the history of Islam (in which devotion to the tawḥīd or Oneness of God led to egalitarianism, justice, and unity) against that of the history of Christianity (in which a stark division between heaven and earth resulted in inequality, violence, and sectarianism) to explain the failures of Christian nations and to develop a basis for his contrasting ideal of a Muslim state. In this article we demonstrate both the power of this historical-theological polemic in its role as anti-colonial narrative as well as the ways in which it limited Iqbāl’s recognition of the potential of Muslim societies to foster similar violence and religiously-based discrimination to that perpetrated by Christian nations.